Special Section: Assessing Information Technologies for Health: Health Technology Assessment - Ammenwerth, E.; Managing Editor for the IMIA Yearbook Section on Assessing Information Technologies for Health (Yearbook of Medical Informatics, 2006)
To summarize current excellent research in the field of health technology assessment.Synopsis of the articles selected for the IMIA Yearbook 2006.Five excellent articles representing the research in four different nations were selected for the IMIA Yearbook 2006 from three international peer reviewed journals.The best paper selection for the Yearbook section ‘Assessing Information Technologies for Health’ presents papers evaluating the benefit and side-effects of information technology in various settings. They clearly indicate that benefit of IT in health care can be achieved when the systems are appropriately designed, implemented and operated. Besides the presented quantitative studies, also qualitative study designs are of value to find unintended effects of IT, or to better explain found effects. IT evaluation supports a reflective practice on how health informatics influences health care, enabling the emergence of an evidence-based health informatics.
Keywords: Medical Informatics; International Medical Informatics Association; Yearbook; evaluation; health technology assessment